Mt. Etna Feeding System and Sliding Flank: A New 3D Image From Earthquakes Distribution in a Customisable GIS - Guardo, R.; De Siena, L.; Dreidemie, C. (Frontiers in Earth Science, 2020)
High-resolution seismic imaging enables the reconstruction of ascending paths of magma and fluids, shallow molten accumulation and flank collapse areas, all crucial information for developing an efficient eruption forecasting strategy. Here, the Marching Cubes algorithm (MC - generally applied to medical visualisation and 3D modelling) is applied to 16 years of earthquake location data at Mt. Etna (Italy). The algorithm defines three-dimensional seismic clusters that take into account seismic location uncertainties and are embedded in a novel volcano-oriented GIS (VolGIS) offering an interpretational environment comprising tomographic images and alternative geophysical models. The results show that a volume of very-low-seismicity is embedded in a high-velocity body, and acts as a zone of transition between transient magmatic events (west) and eastern seismicity related to the sliding eastern flank. The eastern cluster represents the first 3D seismic signature of a deeper flank instability caused by a combination of magmatic and gravitational forces.